AI-17 Response gene to complement-32 expression is upregulated in lupus T cells and promotes IL-17A expression. (August 2018) - Talpos-Caia, Anamaria; Tatomir, Alexandru; Nguyen, Vinh; Cudrici, Cornelia D; Rednic, Simona; Rus, Horea G; Rus, Violeta
Abstract : Background: RGC (Response Gene to Complement)-32 is a cell cycle regulator widely expressed in normal tissues including brain, kidney, spleen, thymus, multiple tumors and in a variety of cell lines. RGC-32 is localized in the cytoplasm and translocates to the nucleus upon upregulation by complement activation, growth factors and cytokines. RGC-32 is induced by TGFβ in fibroblasts, astrocytes and human renal proximal tubular cells and mediates TGFβ dependent profibrotic pathways. RGC-32 is preferentially upregulated in murine Th17 cells and promotes their differentiation. Patients with Systemic Lupus Erythematosus (SLE) display increased serum levels, expanded frequency of IL-17 producing cells. Whether RGC-32 plays a role in human Th17 differentiation pathway and in Th17 abnormalities in lupus patients has not yet been investigated. Methods: RGC-32 expression in naïve CD4 + T cells from normal controls stimulated with cytokines alone or under Th0, Th1, Th2, Th17 and Treg conditions was determined by flow cytometry and RT-PCR. RGC-32 mRNA expression in PBMCs of lupus patients was assessed with the Autoimmune Disease Profiling cDNA Array spotted with cDNA from CD3 +, CD19 + and CD14 + cells and by RT-PCR and flow cytometry. RGC-32 nuclear translocation after stimulation under Th17 conditions was assessed by Western blotting. RGC-32 overexpression and silencing was performed by nucleofection and the effect on IL-17A mRNA levels in CD4 + T cells under Th17 conditions was determined by RT-PCR. Results: RGC-32 mRNA expression was upregulated by TCR stimulation and TGFβ and was more robust under Th17 (3.2±fold) and Treg (2.6±0.8 fold) vs Th1 (1.3±0.4 fold) and Th2 (1.8±0.1 fold) conditions. Moreover, upon stimulation with anti-CD3/CD28 and TGFβ, RGC-32 was translocated into the nucleus. Other cytokines such as IFNα, IL-1β, TNFα did not upregulate RGC-32 mRNA either alone or in combination with TCR stimulation. Overexpression or silencing of RGC-32 in CD4 + T cells upregulated, respectively downregulated IL-17A transcript levels and protein secretion. RGC-32 mRNA and protein level were significantly increased in CD19 + B cells and CD3 + T from lupus patients compared to controls. Conclusions: These results suggest that RGC-32 promotes the differentiation of human Th17 cells. Furthermore, T cells from patients with SLE exhibit increased expression of RGC-32 compared to controls. These data support the idea that RGC-32 signaling may enhance disease expression in SLE by promoting abnormalities in the Th17 pathway and provide a compelling rationale for further investigating the therapeutic potential of blocking RGC-32 in SLE.